Synthesis, structure, and mesomorphism of novel liquid crystalline acrylate monomers and polymers. (2nd January 2016) - Xu, Xiao-Xu; Chao, Chun-Ying; Yao, Xi-Jing
ABSTRACT: A series of novel liquid crystalline monomers (M1 −M8 ) and side chain polymers base polyacrylate backbone were synthesized. The chemical structures were characterized by FT-IR and 1 H-NMR spectra. The mesomorphism and thermal behavior was investigated by polarizing optical microscopy, differential scanning calorimetry, and thermogravimetric analysis. The relationships of structure and mesomorphism are discussed in detail. The eight monomers and their corresponding polymers all show enantiotropic nematic phase. With increasing the spacer length or flexibility of the terminal group, the melting temperature ( T m ) and isotropic temperature ( T i ) of the corresponding monomers and polymers all decreased. However, with increasing the rigidity of the mesogenic core, T m and T i of the corresponding monomers and polymers all increased. TGA showed that all the polymers obtained in this study had excellent thermal stability.